1999
DOI: 10.1159/000054438
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glucocorticoids in the Response of the Hypothalamo-Corticotrope, Immune and Adipose Systems to Repeated Endotoxin Administration

Abstract: The present study was designed to determine whether the glucocorticoid inhibitory feedback mechanism plays a role in the well-known tolerance of the neuroendocrine-immune axis response to repeated endotoxemia. Adult male rats underwent adrenalectomy (ADX) and were implanted with a subcutaneous corticosterone (compound B, CB, 75 mg) pellet, or sham operated and implanted with a placebo pellet. On the morning of day 8 after surgery (experimental day, D1), all rats received an intravenous injection of lipopolysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 36 publications
3
28
0
1
Order By: Relevance
“…In the present study we found that 24-hour fasting mice injected with insulin displayed a significant increase in plasma leptin levels 45 min posttreatment. This increase in leptin levels could well be due to an insulin effect [33], but a contribution of glucocorticoids cannot be discarded [38, 39]since the rise in leptin was preceded by a marked increase in plasma glucocorticoid levels. It has been reported [30]that both adipocyte ob and hypothalamic Ob-Rb mRNAs anticipate (in coincidence with the time of lights off and maximal plasma glucocorticoid levels) the feeding-induced increase in plasma leptin levels by 4 h in freely fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we found that 24-hour fasting mice injected with insulin displayed a significant increase in plasma leptin levels 45 min posttreatment. This increase in leptin levels could well be due to an insulin effect [33], but a contribution of glucocorticoids cannot be discarded [38, 39]since the rise in leptin was preceded by a marked increase in plasma glucocorticoid levels. It has been reported [30]that both adipocyte ob and hypothalamic Ob-Rb mRNAs anticipate (in coincidence with the time of lights off and maximal plasma glucocorticoid levels) the feeding-induced increase in plasma leptin levels by 4 h in freely fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…injection of bacterial lipopolysaccharide (LPS; 150 µg/kg) [27]. This protocol is similar to the one previously validated by our group, although with minor modifications [28]. Blood samples taken were replaced by a similar volume of red blood cells resuspended in artificial plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma samples were split in several aliquots and kept frozen (–80°C) until assayed. Plasma concentrations of glucose [27], triglycerides [27], ACTH [29], corticosterone (B) [30], leptin [27], insulin [31], TNFα [28], IL-10 [28], estradiol [32] and testosterone [32] were determined by specific, previously validated assays.…”
Section: Methodsmentioning
confidence: 99%
“…In 1996, Grunfeld and colleagues [80] reported that hamsters respond to intraperitoneal LPS with increases in both the expression of the leptin gene in white fat and the circulating level of leptin. Since then, the effect of LPS on leptin production has been well characterized in mice and rats [81][82][83][84][85][86][87][88][89][90]. It is now known that: (i) a rise in plasma leptin may occur as early as 1 h post-LPS; (ii) the rise may last for several hours; (iii) the magnitude of the rise is directly proportional to the LPS dose until a ceiling level of leptin is reached; (iv) as in non-inflammatory states, the ceiling level of leptin is ∼20 ng/ml in lean animals, but it may be higher in obese animals; and (v) the leptin response to LPS occurs in both fasted and fed animals, but the peak leptin level achieved in fasted animals is lower, possibly due to their already reduced basal production of leptin.…”
Section: Leptin Production In Inflammationmentioning
confidence: 99%